Kinesin 9 family members perform separate functions in the trypanosome flagellum - Demonchy, Raphaël (The Rockefeller University Press, 2009)
Numerous eukaryote genome projects have uncovered a variety of kinesins of unknown function. The kinesin 9 family is limited to flagellated species. Our phylogenetic experiments revealed two subfamilies: KIF9A (including Chlamydomonas reinhardtii KLP1) and KIF9B (including human KIF6). The function of KIF9A and KIF9B was investigated in the protist Trypanosoma brucei that possesses a single motile flagellum. KIF9A and KIF9B are strongly associated with the cytoskeleton and are required for motility. KIF9A is localized exclusively in the axoneme, and its depletion leads to altered motility without visible structural modifications. KIF9B is found in both the axoneme and the basal body, and is essential for the assembly of the paraflagellar rod (PFR), a large extra-axonemal structure. In the absence of KIF9B, cells grow abnormal flagella with excessively large blocks of PFR-like material that alternate with regions where only the axoneme is present. The functional diversity of the kinesin 9 family illustrates the capacity for adaptation of organisms to suit specific cytoskeletal requirements.